Metabolism of copper. Its consequences for human health - Liudmila Feoktistova Victorava; Yulia Clark Feoktistova (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Several diseases which constitute a health problem for humans worldwide result from failure of copper cellular homeostasis. The mechanism of copper transportation in not completely defined therefore it is necessary to continue deepening on the topic. The present bibliographical review, based on the analysis of 40 scientific articles, describes the processes of copper catchment, distribution and elimination of copper in the cell; it refers, in addition to the diseases related to the metabolic disturbances of this element and its treatment, such as Menkes and Wilson diseases and lastly the molecular studies performed in Cuban patients. It is concluded that this work offers a significant information which contribute to the updating and preparation of the medical personnel regarding these illnesses at the molecular, cellular levels so as in the organism.